The place of marketing activities in the anti-crisis management system - Bahorka, Mariia; Багорка, Марія Олександрівна; Ustik, Tetiana; Устік, Т. В.; Kvasova, Liudmila; Квасова, Людмила Сергіївна (All rights reserved, Publishing House “Baltija Publishing”, 2022)
The aim of the article is to establish the place of marketing in the anti-crisis management of the enterprise, to study the role of the main aspects of anti-crisis marketing in modern enterprises; mastering the components of marketing anti-crisis management of enterprises, to avoid the vulnerability of the enterprise to crisis phenomena and liquidation of their consequences. The methodology basis of the study was a synthesis of the results of applied research in economics, scientific works of domestic and foreign scientists, which highlighted the fundamental theories of competitive advantage, competitiveness and marketing management. Results. The article conducts a study to determine the place of marketing in crisis management of the enterprise, established the role of the main aspects of crisis marketing in modern enterprises; mastered the mechanism of marketing anti-crisis management of enterprises, the purpose of which is to form a strategy for overcoming the crisis and eliminate the consequences of crisis phenomena. Practical results. Taking into account the constant changes in the environment of their operation, enterprises must develop marketing programs that provide for the measures that must be taken to stabilize the situation on the market and get out of the insolvency crisis. Value/ originality. In the authors sense, crisis management should cover all subsystems of enterprise management: operational, technical, financial, and, especially, strategic, marketing, personnel. In the authors sense, crisis management should cover all subsystems of enterprise management: operational, technical, financial, and, especially, strategic, marketing, personnel. It is recognized that marketing in crisis management is not just one of the subsystems of the enterprise, but the basis that ensures the sustainability of all its other units. Метою статті є встановлення місця маркетингу в антикризовому управлінні підприємством, дослідження ролі основних аспектів антикризового маркетингу на сучасних підприємствах; опанування складових маркетингового антикризового управління підприємствами, для уникнення вразливості підприємства до кризових явищ та ліквідації їх наслідків.
Місце маркетингової діяльності в системі антикризового управління
Keywords: anti-crisis management; антикризове управління; anti-crisis marketing; антикризовий маркетинг; marketing activities; marketing activities; anti-crisis program; антикризова програма; marketing strategy; маркетингова стратегія